2007
DOI: 10.1080/13880200701498978
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Anthelmintic Efficacy of an Aqueous Crude Extract ofVernonia amygdalina.

Abstract: The anthelmintic efficacy of an aqueous crude extract of the leaves of Vernonia amygdalina Del. (Compositae) was studied in 16 Nigerian puppies. They were divided into four groups of four puppies per group. The group A animals were uninfected and hence were untreated, whereas those in groups B, C, and D were naturally infected with helminths. Group B animals were untreated whereas group C animals were treated with a proprietary anthelmintic (Mebendazole). Group D animals were treated with aqueous crude extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Following this basic technique, several medicinal plants such as Albizzia lebbek Bentham (Mimosaceae), Allium sativum Linnaeus (Liliaceae), A. santonica Linnaeus (Liliaceae), Cardiospermum halicacabum Linnaeus (Sapindaceae), Coriandrum sativum Linnaeus, Cucurbita mexicana Damm (Cucurbitaceae), Neurolaena lobata Linnaeus (Asteraceae), Perilla frutescens Linnaeus (Lamiaceae), Spigelia anthelmia Linnaeus (Loganiaceae), Spondias mombin Linnaeus (Anacardiaceae), Polyalthia suaveolens Engler & Diels (Annonaceae), Vernonia amygdalina Linnaeus (Asteraceae), and Zingiber officinale Roscoe (Zingiberaceae) have already been documented to show anthelmintic activity against different nematodes of veterinary importance (Akhtar et al, 2000;El Garhy & Mahmoud, 2002;Iqbal et al, 2003;Boonmars et al, 2005;Fujimaki et al, 2005;Ademola et al, 2005Ademola et al, , 2007Eguale et al, 2007;Adedapo et al, 2007). A closely related species of Acacia used in the present study, A. auriculiformis Cunningham extract, reportedly caused significant activity against the nematode Dirofilaria immitis Leidy of dogs (Chakraborty et al, 1995), the bovine nematode Setaria cervi Kunth (Ghosh et al, 1993) and a cestode Hymenolepis diminuta Sturdevant (Ghosh et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Following this basic technique, several medicinal plants such as Albizzia lebbek Bentham (Mimosaceae), Allium sativum Linnaeus (Liliaceae), A. santonica Linnaeus (Liliaceae), Cardiospermum halicacabum Linnaeus (Sapindaceae), Coriandrum sativum Linnaeus, Cucurbita mexicana Damm (Cucurbitaceae), Neurolaena lobata Linnaeus (Asteraceae), Perilla frutescens Linnaeus (Lamiaceae), Spigelia anthelmia Linnaeus (Loganiaceae), Spondias mombin Linnaeus (Anacardiaceae), Polyalthia suaveolens Engler & Diels (Annonaceae), Vernonia amygdalina Linnaeus (Asteraceae), and Zingiber officinale Roscoe (Zingiberaceae) have already been documented to show anthelmintic activity against different nematodes of veterinary importance (Akhtar et al, 2000;El Garhy & Mahmoud, 2002;Iqbal et al, 2003;Boonmars et al, 2005;Fujimaki et al, 2005;Ademola et al, 2005Ademola et al, , 2007Eguale et al, 2007;Adedapo et al, 2007). A closely related species of Acacia used in the present study, A. auriculiformis Cunningham extract, reportedly caused significant activity against the nematode Dirofilaria immitis Leidy of dogs (Chakraborty et al, 1995), the bovine nematode Setaria cervi Kunth (Ghosh et al, 1993) and a cestode Hymenolepis diminuta Sturdevant (Ghosh et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…V. amygdalina also demonstrated appreciable chemotherapeutic activity against Trypanosoma brucei brucei (Igweh and Onabanjo 1989) and Leishmania donovani (Sahpaz et al 1994). There was a significant reduction in the faecal egg count in dogs infected with Toxocara canis and Ancylostoma caninum after the administration of aqueous crude extracts of V. amygdalina (Adedapo et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that botanicals exert similar anthelmintic activity both in vivo and in vitro, usually in a concentration and time-dependent manner (Alawa et al, 2003;Adedapo et al, 2007). In a number of studies, the anthelmintic effects of botanicals against A. galli in poultry were compared to conventional antiparasitic drugs, such as albendazole, levamisole, piperazine, etc, suggesting that botanicals can partially or totally substitute those reference drugs (Akhtar and Riffat 1985, Al-Harbi 2011, Bazh and El-Bahy 2013.…”
Section: Effects On Mobilitymentioning
confidence: 99%